Efek Teripang Terung (Phyllophorus Sp.) Terhadap Kadar HDL Dan LDL Tikus Dengan Diet Tinggi Lemak - ANAK AGUNG ISTRI AGUNG, SRILA NATASWARI; LESTARI DEWI; SOEDARSONO; INDRI NGESTI RAHAYU (Universitas Hang Tuah, 2025)
Cholesterol is divided into two different forms, including HDL (high-density lipoprotein, also referred to as